1994
DOI: 10.1111/j.1939-1676.1994.tb03228.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Of An Additive Solution For Preservation Of Canine Red Blood Cells

Abstract: The effect of an additive preservative solution on canine red blood cell posttransfusion viability (PTV) and on selected canine red blood cell biochemical parameters was studied. One unit (450 mL) of blood was collected from 6 clinically normal dogs into the anticoagulant citrate phosphate dextrose, centrifuged, and the plasma removed. The red blood cells were then suspended in 100 mL of a saline, adenine, dextrose, and mannitol solution and stored at 4'C. Aliquots were removed for study at 1 , 1 0,20,30,37, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 26 publications
1
43
2
Order By: Relevance
“…The mean PTV of canine red blood cells stored in Nutricel for 35 days was 85% with 5'Cr and 90% with 99"T~/5'Cr. This was significantly higher than the mean PTVs of 38% and 36% for the CPDA-1 stored cells as assessed with 5 One unit (450 mL) of blood was collected from each dog and placed into one of two storage solutions. The storage solutions were assigned randomly to samples obtained from study dogs.…”
mentioning
confidence: 69%
“…The mean PTV of canine red blood cells stored in Nutricel for 35 days was 85% with 5'Cr and 90% with 99"T~/5'Cr. This was significantly higher than the mean PTVs of 38% and 36% for the CPDA-1 stored cells as assessed with 5 One unit (450 mL) of blood was collected from each dog and placed into one of two storage solutions. The storage solutions were assigned randomly to samples obtained from study dogs.…”
mentioning
confidence: 69%
“…Although samples of pRBCs were evenly distributed, resultant cellular sedimentation might have caused an increase in RBC, Hct and Hb values (Wardrop et al 1994a;Mudge et al 2004). Furthermore, the increase in Hct values was directly correlated with Table 1.…”
Section: Discussionmentioning
confidence: 92%
“…A previous study, which compared biochemical alterations in rat and human packed RBC (pRBC) stored in CPDA‐1 for 29 days, reported a faster decrease in the pH mean levels, lowering from 7.04 at T0 to 6.64 at T29 in rats and from 7.14 at T0 to 6.50 at T29 in humans. Studies on canine pRBC CPDA‐1 indicate a lower initial pH (between 6.90 and 6.97) at T0 and a significant drop by T35 (between 6.47 and 6.50). One study on canine pRBC units with other storage solutions showed similar trends as those documented in our study (pH range 7.22–7.30 at T1 and 6.99‐7.07 at T31) .…”
Section: Discussionmentioning
confidence: 99%